2009
DOI: 10.1017/s1047951109991831
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric study of disease-related stress, and perceived vulnerability, in parents of children with congenital cardiac disease

Abstract: Parents of children with congenitally malformed hearts can suffer from stress as a result of the medical condition of their child. In this cross-sectional study, we aimed to describe levels of parental stress, and perceived vulnerability, in parents of children who underwent major cardiac surgery, by using both generic and disease-related measures for assessment. We included parents of children who underwent open-heart surgery over the period 2002 through 2007 in the Center for congenital Anomalies Heart Amste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 32 publications
7
92
1
Order By: Relevance
“…The psychological and emotional impact of CHD on parents is well documented [128][129][130][131] and parents' descriptions of their anxiety and symptoms of post-traumatic stress on the online forum corroborate findings in the literature. 132,133 What we were able to additionally elicit, however, were parents' views about the specific challenges they faced following discharge after their child's surgery and their perceptions about what helped mitigate their feelings of isolation and psychological distress.…”
Section: Discussionsupporting
confidence: 76%
“…The psychological and emotional impact of CHD on parents is well documented [128][129][130][131] and parents' descriptions of their anxiety and symptoms of post-traumatic stress on the online forum corroborate findings in the literature. 132,133 What we were able to additionally elicit, however, were parents' views about the specific challenges they faced following discharge after their child's surgery and their perceptions about what helped mitigate their feelings of isolation and psychological distress.…”
Section: Discussionsupporting
confidence: 76%
“…(6)(7)(8)(9) Research findings on parenting stress outcomes in children with CHD are conflicting, with some investigators reporting that parents experienced higher levels of stress, (1,6,7,10,11) whilst others have found stress levels to be similar to those experienced by parents of healthy children; in fact, in some instances parents of children with CHD have even reported lower stress levels than parents of healthy children. It has been suggested that these parents have likely developed a higher threshold for what they perceive to be stressful due to their experiences with their child with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these parents have likely developed a higher threshold for what they perceive to be stressful due to their experiences with their child with CHD. (8,9,11) Research findings suggest considerable variability in individual stress outcomes with disease severity, the changing health status of the child, specific stressors in play at the time and resiliency factors all, in part, explaining the variability. (2,12) In addition, the extent of the burden of care, social isolation and financial difficulties have also been shown to heighten the risk of long-standing psychosocial problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that parents' stress levels are not associated with the severity of the child's illness, but with their ability to cope with the situation (Mörelius et al, 2002, Vrijmoet-Wiersma et al, 2009, Muscara et al, 2015. Parents with poor SOC might focus on the negative emotions and remain hyperaroused at bedtime, which affects their sleep quality.…”
Section: Parents' Sleep Quality Mood and Sense Of Coherence Influencmentioning
confidence: 99%